Spiritual Well-Being and Care Burden in Caregivers of Patients with Breast Cancer in Turkey - Türkben Polat, Hilal (Journal of religion and health, 2023)
This research was carried out to identify the relationship between the spiritual well-being and caregiver burden in caregivers of patients with breast cancer. The study was conducted with family caregivers of patients with breast cancer who presented to the oncology clinic of a university hospital for treatment. The study sample included a total of 138 family caregivers who met the criteria for participation and agreed to participate in the study. The data were collected using a participant information form, caregiver burden scale and three-dimensional spiritual well-being scale. The caregivers have a moderate level of caregiver burden and their spiritual well-being was quite high. The caregiver burden of female caregivers was found to be significantly higher than that of male caregivers (p = 0.040). There is a negatively significant relationship between caregiver burden and spiritual well-being (p = 0.000, r =  − 0.357). The caregiver burden is significantly higher among the 24-h caregivers compared to that among the 3-h and 4-6-h caregivers (p = 0.003). The spiritual well-being of the caregivers who provide care between 3 h and 4-6 h a day was significantly higher than that of those who provide 24-h care (p = 0.001). Increasing spiritual well-being may help to reduce caregiver burden in caregivers of those with breast cancer.